Pericardial fat from a single horizontal long axis cardiac magnetic resonance cine image: a validation study against three-dimensional cardiac computed tomography. (3rd October 2022) - Zamani, S K; Aldiwani, H; Razipour, A; Wei, J; Kwan, A C; Berman, D S; Dey, D; Bairey Merz, C N; Nelson, M D
Abstract: Background: Excess fat accumulation around the heart (i.e., pericardial fat) is positively associated with cardiovascular disease. Pericardial fat is composed of two distinct depots: (1) epicardial fat, which is a metabolically active adipose tissue located between the heart and the pericardium, and (2) paracardial fat, which is the fat deposit in the mediastinum outside of the parietal pericardium. Both depots are visible on the horizontal long axis cardiac magnetic resonance (CMR) cine (i.e., four chamber view), offering an attractive opportunity to quantify pericardial fat from standard CMR cine images. Purpose: To validate pericardial fat area measured from a single horizontal long axis CMR cine against whole-heart volumetric non-contrast cardiac computed tomography (CT) measurements. Methods: To accomplish our goal, we leveraged 25 cases from the Women's Ischemia Syndrome Evaluation – Coronary Vascular Dysfunction Continuation cohort who underwent both cardiac MRI and cardiac CT within a median of 35 days apart. For MRI, pericardial fat area was measured from a single high resolution steady state free precession cine image in the horizontal long axis imaging plane using commercially available software (CVI42 V5.13.5, Circle Cardiovascular Imaging, Figure 1A). For CT, pericardial fat volume was measured using a fully automated deep learning algorithm (QFAT 2.0, Figure 1A). Results: Fat area measured from a single horizontal long axis cine image was closely related to fat volume measured by three-dimensional cardiac CT, with strong correlations for epicardial fat (R2=0.72, p<0.01, Figure 1B), paracardial fat (R2=0.80, p<0.01, Figure 1C), and pericardial fat (R2=0.91, p<0.01, Figure 1D). Conclusions: Measuring pericardial fat area, and its constituent parts, from a single horizontal long axis cine image is both feasible and strongly related to reference standard pericardial fat volume by cardiac CT. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): National Institutes of Health